2018
DOI: 10.3389/fpsyg.2018.01038
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Opinion About a Virtual Reality System as an Adjunct to Psychological Treatment for Stress-Related Disorders: A Quantitative and Qualitative Mixed-Methods Study

Abstract: This study aims to explore patients’ and therapists’ attitudes about the psychological treatment they received (patients) or applied (therapists). The treatments were standard CBT protocols for post-traumatic stress disorder (PTSD), complicated grief (CG), or adjustment disorders (ADs), depending on each patient diagnosis. The treatments were delivered following a traditional format or supported by a virtual reality (VR) system “EMMA’s WORLD” designed for the treatment of stress-related disorders. “EMMA’s WORL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…Service users supported novel methods of engagement of people who may be suffering in isolation and found virtual worlds to delivery therapy acceptable. This finding is consistent with previous studies that employed similar delivery methods (Brewer et al, 2017;Guillén, Baños, & Botella, 2018;Rosal et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Service users supported novel methods of engagement of people who may be suffering in isolation and found virtual worlds to delivery therapy acceptable. This finding is consistent with previous studies that employed similar delivery methods (Brewer et al, 2017;Guillén, Baños, & Botella, 2018;Rosal et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, EMMA’s World has been found to be well accepted by both patients and therapists. It helped to foster motivation in patients, while helping the therapist to apply the treatment [26]. Thus, VR can be also useful as an adjunct tool to enhance the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mindfulness training already referred to, studies have shown that VR has been used for managing the well-being of dementia patients (Rose et al 2018). Guillén et al (2018) have also highlighted the possibilities and importance of customizable VR content for enhancing stress-management therapy with positive usability results and feedback from participants. VR research focusing on restorative and relaxation applications (Blum et al 2019;Valtchanov et al 2010;Roche et al 2019) has also shown useful and positive findings in improving mental wellness, especially in the context of physical illness or disability.…”
Section: Future Directionsmentioning
confidence: 99%